Model Kepemimpinan Kepala Kantor Kementerian Agama Kota Manado Dalam Meningkatkan Kinerja Pegawai - Aljuanika Ering; Aldie Mandey; Astrid L. Mandas (Journal Of Psychology humanlight, 2023)
This research aims to 1) find out and describe the leadership model of the head of the Manado city ministry of religion in improving employee performance 2) find out and describe the inhibiting factors of the leadership model of the head of the Manado city ministry of religion in improving employee performance 3) find out and describe the inhibiting factors of the leadership model Head of Manado City Ministry of Religion office in improving employee performance. The research approach used is qualitative research with data collection through observation, interviews and documentation. The results of the research analysis found that the leadership model implemented by the head of the Manado City Ministry of Religion office was transformational leadership. However, this leadership model is still weak so that the provision of motivation and encouragement to employees is not optimal which also results in employee performance not being carried out well, for example being late for work, employees who are inconsistent with their working hours schedule, facilities that are still inadequate, supervisory supervision in management of infrastructure is not yet optimal. 2). Factors inhibiting the transformational leadership of the head of office in improving employee performance at the Office of the Ministry of Religion, Manado City. Employees often cover themselves when there are problems, employees are less optimistic in carrying out their work, less confident in solving the problems they face. 3). Supporting factors in the transformational leadership of the head of office in improving employee performance at the Office of the Ministry of Religion, Manado City, namely having an enthusiastic nature, good cooperation between employees, and caring about work. This can be seen from attendance, discipline, work motivation, and work commitment.